Double inferior vena cava with multiple interconnections – a rare case report - Kumar, Sushil; Baidya, Ritwik; Baral, Prakash (Journal of Gandaki Medical College-Nepal, 2020)
Duplication of the inferior vena cava (IVC) has been estimated to occur in 0.2% to 3% of the population. Although rare, the presence of double inferior vena cava is important to recognize as it has important implications. Diagnostic confusion in interpreting imaging results can arise when a venous anomaly is mistaken for a pathologic process like lymphadenopathy. If such patient were to need an IVC filter placement, separate filters would be required, one for the right and one for the left IVCs. A vascular surgeon would need to be aware of these anomalies to perform safe surgery of the retroperitoneal organs. We present a case of duplicated IVC, which was observed during routine dissection of a 58-year-old male cadaver. Left IVC was communicating with left renal vein superiorly. The left renal vein was running obliquely behind the abdominal aorta. Also, the left IVC was connected to right IVC by one transverse anastomosing vessel. The two-retroaortic communication between right and left IVC make this case report unique.